Impacted Palatal Canines and Diode Laser Surgery: A Case Report - Marina Consuelo Vitale; Maria Gloria Nardi; Matteo Pellegrini; Francesco Spadari; Federica Pulicari; Roberto Alcozer; Martina Minardi; Maria Francesca Sfondrini; Karin Bertino; Andrea Scribante (Case Reports in Dentistry)
Introduction. Maxillary canine is the most frequent dental element that could likely remain impacted in the bone structure, with a percentage between 1 and 5%. This study presents a case report using a diode laser for surgical-orthodontics disinclusion of a palatal mucosal impacted permanent left upper canine (2.3) and the simultaneous application of an orthodontic bracket. Methods. After cementation of the trans-palatal bar to the upper first molars with a hook for orthodontic traction, local anaesthesia with articaine was performed, followed by surgical operculectomy using a diode laser (810 nm wavelength, continuous wave mode with a power output of 3 W, and a 0.4 mm diameter optical fiber), and the orthodontic bracket with a passive metal looped ligature was applied. Subsequently, active elastic traction was applied on 2.3 and the upper arch was bonded for the application of a series of orthodontic wires, lace-back, and metal ligatures. A progressive reactivation of the elastic traction and extraction of 6.3 was necessary to translate the canine into the correct arch position. Results. Diode laser surgical-orthodontic disinclusion of impacted upper canine was performed successively, resulting in a dry surgical field ideal for orthodontic bracket adhesion. No pain and no swelling have been reported from the patient. The orthodontic treatment allowed the canine to be moved to the correct position in the arch. Conclusions. This case showed that the diode laser is a valid alternative for the surgical-orthodontic disinclusion of an included tooth element.